Properties of the Characteristic Polynomials of Pn and Cn - Abdul-Jabbar, Nuha (Al-Nahrain Journal of Science, 2011)
In this paper, the computational formula for the generalized characteristic polynomials of graphs Pn and Cn are found. Also, we show the relation between the vertices and edges of the graphs and the coefficients of the characteristic polynomials. Finally, the eigenvalues of the polynomials are computed and their properties are studied.